2023
DOI: 10.1002/cctc.202300330
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Promiscuity of Horseradish Peroxidase: Aerobic Oxidative Regeneration of Oxidized Nicotinamide Cofactors

Abstract: NAD(P)+ regeneration is of great importance for dehydrogenase (DH)‐catalyzed oxidations. In this work, we report horseradish peroxidase (HRP)‐catalyzed aerobic oxidation of the reduced nicotinamide cofactors, including natural and non‐natural ones, into the oxidized form at neutral and alkaline pH enabled by external amino acids (AAs). HRP showed promiscuous yet extremely low oxidase activity toward NADH at pH 7 in the absence of both AAs and mediators, as evidenced by the observation of compound III. The mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 68 publications
0
7
1
Order By: Relevance
“…46 Intermediate compound I was not observed in this work, likely due to its labile nature. In terms of the mechanism, therefore, aerobic NADH oxidation by the HRP/ Mn 2+ /mediator system is distinct from that by the HRP/AA/ mediator system reported recently by us, 31 as oxidase intermediate compound III instead of compound I/II is involved in the latter. The distinctions between the two systems may be partially rationalized by their catalytic mechanisms.…”
Section: ■ Results and Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…46 Intermediate compound I was not observed in this work, likely due to its labile nature. In terms of the mechanism, therefore, aerobic NADH oxidation by the HRP/ Mn 2+ /mediator system is distinct from that by the HRP/AA/ mediator system reported recently by us, 31 as oxidase intermediate compound III instead of compound I/II is involved in the latter. The distinctions between the two systems may be partially rationalized by their catalytic mechanisms.…”
Section: ■ Results and Discussioncontrasting
confidence: 64%
“…More than 60 years ago, several groups reported that NAD­(P)H was aerobically oxidized by HRP in the presence of Mn 2+ and mediators. In this work, the “old” chemobiocatalytic NAD­(P) + oxidation reaction was revisited along with the expansion of its substrate scope; a putative mechanism was proposed on the basis of the results obtained herein and previous literature. Notably, the efficiency of the present system involving Mn 2+ is much higher than that of a recent system involving AAs, evidenced by the reaction periods required for almost complete substrate conversion at the same substrate concentration (approximately 1 vs 25 min). More importantly, the application potential of this system was demonstrated in DH-catalyzed (cascade) oxidation and photobiocatalysis.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…42 Recently, an in vitro stable ALDH from Pseudomonas aeruginosa ( Pa ALDH) was identified by our group, and it showed good activities toward a variety of aromatic aldehydes. 58 To test whether the enzyme is tolerant toward photocatalysis inactivation, Pa ALDH was merged with EY@NKA for photoenzymatic oxidation of furfural (the first step in Scheme 2), 59 in which EY@NKA served as a catalyst for both photocatalytic NADP + recycling and FCA photooxygenation. Fig.…”
Section: Resultsmentioning
confidence: 99%